2017
DOI: 10.1007/s11356-017-0863-8
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about exposure of Iranians to cadmium? Findings from a systematic review

Abstract: Cadmium is an important environmental contaminant. High consumption of chemical fertilizers and industrial activities in recent decades has caused people to be worried about exposure to cadmium. There is no policy for environmental and biological monitoring of exposure to cadmium in the general population in Iran. This study was aimed to review cadmium content in consuming foods and biological samples in Iran, systematically. We developed a comprehensive search strategy and used it to search on Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Monitoring cadmium exposure in the Iranian population indicated that cadmium contamination occurred in food groups, such as rice, cereals, legumes, and vegetables. Specifically, 75% of the consumed rice samples showed cadmium concentrations higher than the maximum cadmium limit (0.06 mg⸱kg −1 ) allowed by the Institute of Standards and Industrial Research of Iran (ISIRI) [ 51 ]. In addition, canned fish (mean: 0.032 μg·g −1 ) and tuna (mean: 0.022 μg·g −1 ) samples showed high cadmium concentrations (ISIRI: 0.05 mg⸱kg −1 ) [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring cadmium exposure in the Iranian population indicated that cadmium contamination occurred in food groups, such as rice, cereals, legumes, and vegetables. Specifically, 75% of the consumed rice samples showed cadmium concentrations higher than the maximum cadmium limit (0.06 mg⸱kg −1 ) allowed by the Institute of Standards and Industrial Research of Iran (ISIRI) [ 51 ]. In addition, canned fish (mean: 0.032 μg·g −1 ) and tuna (mean: 0.022 μg·g −1 ) samples showed high cadmium concentrations (ISIRI: 0.05 mg⸱kg −1 ) [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium has no biological function in plant growth but is readily accumulated in all plants and edible parts of crops through the metabolic pathway of essential nutrients for the plants, such as Zn and Fe. Thus, by entering human beings' and animals' food chains, it may cause a wide variety of acute and toxic effects [144].…”
Section: Phytoremediation Nanoparticles and Microbial Fermentation Against Cadmium Toxicitymentioning
confidence: 99%
“…In present study, BUN and Scr were used to evaluate the glomerular function and β 2 -MG to assess the renal tubular damage (24). Elevated BUN indicates substantial renal lesions (25) (such as glomerulonephritis).…”
Section: Discussionmentioning
confidence: 98%